Students’ Attitudes Toward Physics and Its Influencing Factors: A Literature Review - Kurniawan, Aris; Kuswanto, Heru (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This literature study aims to address factors that influence students' attitudes towards physics and variations in learning methods that can be a reference for teachers to enhance students' attitudes towards physics. This study used systematic literature review method. Literature review was conducted using the keyword